2020
DOI: 10.1186/s13054-020-03351-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating bioactive adrenomedullin as a marker of sepsis, septic shock and critical illness

Abstract: Background Biomarkers can be of help to understand critical illness and to identify and stratify sepsis. Adrenomedullin is a vasoactive hormone, with reported prognostic and potentially therapeutic value in sepsis. The primary aim of this study was to investigate the association of circulating bioactive adrenomedullin (bio-ADM) levels at intensive care unit (ICU) admission with mortality in sepsis patients and in a general ICU population. Secondary aims included the association of bio-ADM with organ failure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
5
25
2
Order By: Relevance
“…This could be explained by the sensitivity of the assay used in each study, indicating that the cut-off values obtained by different assay methods may be different. Recently, Lundberg et al [20] reported a Yuden's index cut-off of 45 pg mL -1 for predicting the 28-day sepsis-related mortality in their sepsis cohort, which was as low as in the present study.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…This could be explained by the sensitivity of the assay used in each study, indicating that the cut-off values obtained by different assay methods may be different. Recently, Lundberg et al [20] reported a Yuden's index cut-off of 45 pg mL -1 for predicting the 28-day sepsis-related mortality in their sepsis cohort, which was as low as in the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…In some previous studies, the levels of total AM were assessed and their utility in diagnosing sepsis was compared with those of other chemical biomarkers, such as CRP, PCT, lactate, and PSEP [8,9,18,20,[24][25][26]. We found that among all the clinical parameters examined, the diagnostic accuracy for sepsis on the rst day of ICU admission was the highest for total AM, and that of mature AM was the second highest.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…13 The 99th percentile of bio-ADM is 43 pg/mL in a normal population. 27 In DPP3 samples of 355 healthy subjects, the 97.5th percentile was 43 ng/mL (personal communication with SpingoTec GmbH).…”
Section: Data Sourcesmentioning
confidence: 99%
“…26 A study by Lundberg et al found admission bio-ADM to be associated with 30-day mortality and organ failure in sepsis patients as well as in a general ICU population. 27…”
Section: Introductionmentioning
confidence: 99%